Wind flow characteristics through shrouded wind turbine using ANSYS - Alzgool, Mais; Alrefai, Obada; Alamleh, Ahmad; Alyaqoub, Mohammad (Edelweiss Applied Science and Technology, 2024)
Wind energy is a mature and quick-growing source of energy in many nations. New wind energy technologies must be introduced to increase effectiveness and reduce the cost of wind turbine installation. Wind energy conversion experts believe that shrouded wind turbines are a promising technology that could raise output and efficiency levels. A low-pressure zone is created behind the turbine because of the shroud’s unique structure. As a result, the turbine draws in greater mass flow to produce more power. With the aid of this innovative technology, wind turbines could be used in populated areas where lower wind speeds could be captured. In this study, a comparative analysis has been applied to different designs of shrouded wind turbines to analyze the wind speed, pressure, output power and power coefficient. ANSYS software has been conducted in this paper where the results obtained that the output power could be increased up to 3-4 times compared to the bare wind turbine, also a high-power coefficient could be reached up to 83.1%.